Urban Matters : Current Approaches in Variationist Sociolinguistics. - Ziegler, Arne. (Studies in Language Variation Series, 2021)
This volume discusses the characteristics and dynamics of urban language use, considering aspects such as contact, variation and change, as well as identity, indexicality, attitudes, and spatial factors including mobility, (counter-)urbanisation and diffusion processes. It presents modern methodological and conceptual ideas as well as new findings.